Implementasi Blueprint Untuk Optimalisasi Keamanan Jaringan Dengan Firewall Menggunakan Metode Network Development Life Cycle - Ina Rai Sae; Krisantus Jumarto Tey Seran; Kristoforus Fallo (Justek : Jurnal Sains dan Teknologi, 2025)
The development of information and communication technology has become an important element in supporting all organizational activities, one of which is a religious institution such as GMIT Petra Kefamenanu. This church utilizes the internet network to support worship activities, administration, and educational services. However, the increasing needs and number of users cause slow connections and the emergence of network security risks. Based on these conditions, this study aims to design and implement an optimal and secure network infrastructure blueprint using a firewall as a network security system and a Network Development Life Cycle (NDLC) approach as a development method. This research was conducted through five NDLC stages: network requirements analysis, design, blueprint , simulation using Cisco Packet Tracer , configuration implementation with Mikrotik, and monitoring. The results of the study show that the network design based on star technology (star topology) and firewall configuration that includes DHCP, NAT, and Layer 7 Protocol features successfully increased overall security and connection efficiency. The firewall is able to limit unproductive access and prevent potential cyber threats. This implementation proves that the blueprint is designed not only for a systematic and extensive network structure, but also provides comprehensive network protection against external attacks, thus supporting more effective church services.